The Rise of Political Hatred in Twitter Conversations of Indonesian Netizens - Iswandi Syahputra (Ikatan Sarjana Komunikasi Indonesia, 2021)
This article discusses expressions of hatred as a political category that has become a topic of discourse among Indonesian netizens on Twitter. The Twitter conversations data used in this analysis were obtained through a Twitter thread reader application operated by DEA (Drone Emprit Academic). As a political category, hatred is considered new. It emerged as and became a conversational topic for netizens on Twitter due to various political promises President Joko Widodo has made during his campaign and has not fulfilled. Political hatred has spread extensively owing to Twitter leading to absolute freedom of expression. On Twitter, political hatred has increased because of two main clusters during the 2019 Presidential Election campaign. The two clusters represent two pairs of presidential and vice-presidential candidates, namely Joko Widodo-Ma’ruf Amin (Number 01/JKW-MA) and Prabowo Subianto-Sandiaga Uno (Number 02/PS-SU). This study may have implications on broader hatred-based political conflict. Additionally, political hatred may also have implications on the waning of the public’s function to criticize political actors and the government because criticism may be suppressed on the basis of it being an expression of hatred. This will, accordingly, turn into a new dilemma in a democratic country, between freedom of expression and potential rise of new authoritarianism.